Copia librorum: Problemgeschichte imaginierter Bibliotheken 1580-1630 - Werle, Dirk (Frühe Neuzeit, 2012)
The study investigates imaginary libraries in literary works of the 16th and 17th centuries and their status in the context of the history of ideas. Since the invention of printing there had been a headlong increase in the production of texts, accompanied by a corresponding information overload. These were the preconditions required for certain feats of the imagination to become possible in the first place. In the form of thought-experiments, contemporary literary figures and scholars attempted to outline solutions for the urgent problems involved in imposing order on the unmanageable plethora of texts and assuring the progress of knowledge in the face of the untrammeled abundance of factual information.